A DSRC-based vehicle-road collaboration system for microscopic traffic simulation platform - Gu, Haowen (Nanyang Technological University, 2020)
With the rapid development of society, automobiles have become an essential part of our daily life. To prevent related social problems like traffic congestion and traffic accidents, vehicle-road collaboration system based on Dedicated Short-Range Communications (DSRC), a research branch in Intelligent Transportation System, is being explored. In this dissertation, the application value of a DSRC-based vehicle-road collaboration system is studied by the simulation of Vehicle-to-Vehicle (V2V), Vehicle-to-Roadside(V2R), and Roadside-to-Roadside (R2R) communication. A road network is established in VISSIM to perform traffic simulation. The software also provides comprehensive data to realize the information exchange in V2V, V2R and R2R communication. MATLAB, as the main control software, commands the simulation process in VISSIM via VISSIM-COM, according to DSRC protocol. Both system operation mechanism and model construction on two platforms are explained in detail. Finally, three applications of vehicle-road collaboration system, which are useful in real traffic, are simulated to verify the value of DSRC communication in the system on traffic safety and efficiency.